Larvae of two species of Trizocheles (Decapoda: Anomura: Paguroidea: Pylochelidae: Trizochelinae), description of the adult of one, and preliminary implications of development on pylochelid phylogeny - Mclaughlin, Patsy A.; Lemaitre, Rafael (Zootaxa, 2008)
The larvae of two species of the pylochelid genus Trizocheles are described from prematurely hatched specimens and compared with earlier described larvae of Pylocheles (Pylocheles) and Pomatocheles. Although all are lecithotrophic and exhibit marked advanced development, differences in the larval morphology among the three genera are profound. Consideration is given to these differences as they relate to development in the entire Paguroidea, and the possible impact they may have on pylochelid phylogeny. As one of the Trizocheles species is undescribed, adults as well as larvae are described and illustrated.